Bronchial asthma in children of Ukraine: medical and environmental parallels of morbidity and prevalence - Volosovets, O. P.; Bolbot, Y. K.; Kryvopustov, S. P.; Mozyrska, O. V.; Kryvopustova, M. V.; Prokhorova, M. P.; Kupkina, A. V. (Medicni Perspektivi, 2020)
Bronchial asthma is one of the most common non-infectious diseases of children worldwide. More than half of such clinical cases may lead to functional disability and significantly affects the quality of life of a sick child. The aim of the study was to research trends in the incidence and prevalence of bronchial asthma among children in different regions of Ukraine over the past 25 years and assess the effect of air pollutant emissions from stationary sources in the region of children residence on the incidence and prevalence of bronchial asthma among them. According to the Center for Medical Statistics of the Ministry of Health of Ukraine, the incidence of bronchial asthma among children aged 0-17 years was 4513 0.59 of new cases per 1000 population in 2017. Prevalence of this disease was 37246 cases (4.91 per 1000 population). The majority of newly diagnosed bronchial asthma cases was observed in children aged 7-14 years – 2439 or 54.0% of the total, which is in line with global trends. The highest incidence and prevalence in all three age groups was observed among children of Kyiv and Kharkiv, Zaporizhia, Vinnitsa, Dnipropetrovsk, Donetsk regions. We have discovered a direct and close connection (ρ=0.741) between the reduction of air pollutant emissions from stationary sources and decreasing of the prevalence of bronchial asthma among children in recent years. Over the past 25 years in Ukraine there has been 69.3% increase in prevalence and 22.9% increase in incidence of bronchial asthma among children. Predominance of detecting this pathology was in the group of children from large industrial and agro-industrial regions of the country with significant volumes of atmospheric pollutants from stationary sources of pollution.